Interference Among Group A Arboviruses - Zebovitz, Eugene (1968)
Interference among group A arboviruses is described which does not involve the mediation of interferon. Interference was observed only if the interfering virus had an advantage over the challenge virus, either in time or in multiplicity of infection. Adsorption, penetration, and uncoating of challenge virus did not appear to be inhibited, but the synthesis of infectious viral ribonucleic acid of the challenge virus was significantly retarded. It was shown with temperature-sensitive viruses or mutants that the replication of viral ribonucleic acid by the interfering virus was required to establish interference. A mechanism of interference based on a competition for replication sites or substrates is compared with other possible explanations.